Społeczna odpowiedzialność w przywództwie - Karaszewski, Robert; Karwacka, Marta (Social Responsibility in Leadership, 2009)
For several years we have witnessed the growing interest of entrepreneurs in corporate social responsibility. Reports on the social involvement of large international businesses as well as small companies have reached to us more frequently. Because the ethics of business and social responsibility are the subject of interest of an increasing number of corporations, it is worth considering, what the role of leaders in the popularization of this concept is. It seems that leaders managing a group of employees are indispensable in the implementation of ethical principles within businesses. Leaders are responsible not only for the financial results of the functioning of groups managed by them, but also for the establishment and popularization of moral standards.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 48-58